Skill set or mind set? Associations between health literacy, patient activation and health. - Samuel G Smith; Laura M Curtis; Jane Wardle; Christian von Wagner; Michael S Wolf (PLoS ONE)
Objective There is ongoing debate on whether health literacy represents a skill-based construct for health self-management, or if it also more broadly captures personal 'activation' or motivation to manage health. This research examines 1) the association between patient activation and health literacy as they are most commonly measured and 2) the independent and combined associations of patient activation and health literacy skills with physical and mental health. Methods A secondary analysis of baseline cross-sectional data from the LitCog cohort of older adults was used. Participants (n = 697) were recruited from multiple US-based health centers. During structured face-to-face interviews, participants completed the Test of Functional Health Literacy in Adults (TOFHLA), the Patient Activation Measure (PAM), the SF-36 physical health summary subscale, and Patient Reported Outcomes Measurement Information Service (PROMIS) short form subscales for depression and anxiety. Results The relationship between health literacy and patient activation was weak, but significant (r = 0.11, p<0.01). In models adjusted for participant characteristics, lower health literacy was associated with worse physical health (β = 0.13, p<0.001) and depression (β = -0.16, p<0.001). Lower patient activation was associated with worse physical health (β = 0.19, p<0.001), depression (β = -0.27, p<0.001) and anxiety (β-0.24, p<0.001). Conclusions The most common measures of health literacy and patient activation are weakly correlated with each other, but also independently correlated with health outcomes. This suggests health literacy represents a distinct skill-based construct, supporting the Institute of Medicine's definition. Deficits in either construct could be useful targets for behavioral intervention.